Implementation of Project Based Learning Model to Improve the Learning Results of Economic Subjects of SMA Negeri 15 Semarang - Komar, Zaenul; Rusdarti, Rusdarti; Khafid, Muhammad (Journal of Economic Education, 2021)
Market material is an economic subject matter in the study of more using lectures and memorization. This leads to a lack of ability for students to develop their potential and make students tend to be passive. Therefore, it takes a learning model that able to make students more active in learning. One of the learning models that can improve the quality and results of the economic learning of Model Project Based Learning (PjBL) with a Scientific approach. The purpose of this study is to know the Project Based Learning model is more effective in improving the results of the study of economic subjects of SMA Negeri 15 Semarang. This research used experimental research with nonequivalent control group design. The method of collecting data in this study used observation methods and tests. The population number in this study was 108 students. Based on the results of the analysis, an increase in the learning outcomes of economic subjects for the experimental group amounted to 27.31% with an average score of 89.36 and an increase in the learning outcomes of economic subjects for the control group of 10.79% with an average score of 77.00. This shows that the Project Based Learning Model is more effective than conventional learning model or lecture in improving the results of the study of economic subjects of SMA Negeri 15 Semarang.